Perancangan Sistem Smart Resto Mobile Reservation Client Server Multiplatform - Satria Satria (Sekolah Tinggi Teknik - PLN, 2020)
Waroeng Steak And Shake is one of the favorite restaurants of Bekasi residents which in serving and payment ordering services is still using the manual method by taking notes on paper. This method is very ineffective because it still uses a lot of paper to record orders and cause long customer queues just to order food or pay for orders. Customers cannot provide special notes directly to the chef so orders are made according to standards. To overcome the problem of the length of the queue and the use of a lot of paper and customers can provide notes directly to the chef, the authors propose to design a smart resto mobile multiplatform server client-server system with the waterfall method. The author hopes that this method can be implemented well in the system of ordering service records directly to the chef and of course reduce the queue at Waroeng Steak And Shake restaurant in Bekasi